The Federal Democratic Republic of Ethiopia : Joint Staff Assessment of the Poverty Reduction Strategy Paper Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2004)
This report reviews the Joint Staff Assessment of the Poverty Reduction Strategy Paper Annual Progress Report for The Federal Democratic Republic of Ethiopia. It summarizes the Sustainable Development and Poverty Reduction Program (SDPRP), which is the Poverty Reduction Strategy Paper for Ethiopia. The staff of the Bank and IMF considers that Ethiopia's efforts toward implementation of the strategy provide sufficient evidence of its continuing commitment to poverty reduction, and therefore the strategy continues to provide a credible framework for World Bank and IMF concessional assistance.